Methodological Perspectives in the Teaching of Subjects Related to the Classical World - Sancho Montés, Susana (Avances en Supervisión Educativa, 2025)
The current rules in the Spanish education system establish the teaching of Classical Culture and Latin in Compulsory Secondary Education (Educación Secundaria Obligatoria), and Latin and Greek in Baccalaureate (Bachillerato). In this article, we try to study the different methodological approaches that have been used by teachers until the present time. We have proceeded to review them: from the so-called traditional methodology to the active methodologies. The final part of the article focuses on the most innovative strategies such as the use of the flipped classroom, project-based learning (PBL), gamification or cooperative learning, don’t forgetting at all the use of didactic resources such as the use of new technologies and Artificial Intelligence in the teaching of Latin, Greek and Classical Culture. The conclusion reached is the need to make use of all the didactic resources and active methodologies available to teachers, always encouraging critical thinking.
Keywords: Active methodologies; flipped classroom; PBL; gamification; cooperative learning; Internet; Artificial Intelligence; teaching resources